Penerapan Teori Belajar Konstruktivisme melalui Model PAKEM dalam Permainan Bolavoli pada Sekolah Menengah Pertama - Pinton Setya Mustafa; Roesdiyanto Roesdiyanto (Jendela Olahraga, 2021)
The purpose of this article is to provide information about learning that adheres to the theory of constructivism through the active, creative, effective, and fun learning model (PAKEM) in volleyball game material in grade VII Junior High School. Constructivism learning theory provides opportunities for students to build their own conceptual knowledge through teacher facilitation. Physical education, sports, and health (PESH) learning activities involve moving activities to achieve competence. The volleyball game is one of the materials used in learning PESH movements. The principle of learning PESH is to involve students to be active and enjoy when doing physical activities. The PAKEM model is an alternative that can be used in volleyball learning for seventh grade students of junior high school. The PAKEM model helps students build their own knowledge through the variety of lessons the teacher provides. In conclusion with the PAKEM model students can be active, creative, effective, and happy while learning volleyball in PESH is presented. Teachers need to innovate continuously to design learning models that are appropriate to the characteristics of students.Keywords:constructivism learning theory, PAKEM, physical education, volleyball  AbstrakTujuan dari artikel ini adalah memberikan informasi tentang pembelajaran yang menganut teori konstruktivisme melalui model pembelajaran aktif, kreatif, efektif, dan menyenangkan (PAKEM) dalam materi permainan bolavoli pada kelas VII Sekolah Menengah Pertama. Teori belajar konstruktivisme memberikan kesempatan kepada peserta didik untuk membangun sendiri pengetahuan konseptual melalui fasilitasi guru. Aktivitas pembelajaran pendidikan jasmani, olahraga, dan kesehatan (PJOK) pelaksanaan melibatkan kegiatan bergerak untuk mencapai kompetensi. Permainan bolavoli merupakan salah satu materi yang menjadi dalam pembelajaran gerak PJOK. Prinsip pembelajaran PJOK adalah melibatkan siswa untuk aktif dan senang ketika aktivitas melakukan fisik. Model PAKEM merupakan salah satu alternatif yang dapat digunakan dalam pembelajaran bolavoli pada siswa kelas VII SMP. Model PAKEM membantu siswa membangun pengetahuannya sendiri melalui variasi pembelajaran yang disajikan oleh guru. Kesimpulannya dengan model PAKEM siswa dapat aktif, kreatif, efektif, dan senang selama pembelajaran bolavoli dalam PJOK disajikan. Guru perlu melakukan inovasi secara berlanjut untuk merancang model pembelajaran yang sesuai dengan karakteristik peserta didik.Kata kunci:teoribelajar konstruktivisme, PAKEM, pendidikan jasmani, permainan bolavoli